Longitudinal changes of right ventricular deformation mechanics during trastuzumab therapy in breast cancer patients. (27th February 2019) - Keramida, Kalliopi; Farmakis, Dimitrios; Bingcang, Jose; Sulemane, Samir; Sutherland, Stephanie; Bingcang, Roma A.; Ramachandran, Kanchana; Tzavara, Chara; Charalampopoulos, Georgios; Filippiadis, Dimitrios; Kouris, Nikolaos; Nihoyannopoulos, Petros
Abstract : Background: Trastuzumab improves dramatically the prognosis of HER2‐positive breast cancer patients, but it may lead to cardiotoxicity with left ventricular (LV) systolic dysfunction. Its effects on right ventricular (RV) function have not however been elucidated. We sought to assess LV and RV deformation mechanics during treatment with trastuzumab in breast cancer patients. Methods and results: We studied 101 consecutive women (mean age 54.3 ± 11.4 years) receiving trastuzumab for 12 months; 62 of them (61.4%) had previously received anthracyclines and 26 (25.7%) were receiving taxanes concurrently with trastuzumab. Comprehensive two‐dimensional echocardiography with speckle tracking imaging of LV and RV global longitudinal strain (GLS) and RV free wall longitudinal strain (FWLS) analyses were performed at baseline and every 3 months up to treatment completion. Cardiotoxicity was defined as a decrease of baseline LV ejection fraction > 10 percentage units to a value < 50%. At 3 months, only LV GLS was significantly reduced (−19.5 ± 2.7 to −18.7 ± 2.8, P = 0.0410), while at 6 months, LV GLS, RV GLS and RV FWLS had significantly declined reaching their lowest values (−17.9 ± 6.1, P = 0.002, −19.6 ± 5.2, P = 0.003 and −19.7 ± 5.6, P = 0.004, respectively). Ten women (9.9%) developed cardiotoxicity. A RV GLS percent change of −14.8% predicted cardiotoxicity with 66.7% sensitivity and 70.8% specificity (area under the curve 0.68, 95% confidence interval 0.54–0.81), classifying correctly 90% of women with cardiotoxicity. This cut‐off is quite similar to the 15% change of LV GLS previously suggested as predictive of cardiotoxicity. Conclusions: Deformation mechanics of both the left and right ventricle follow similar temporal pattern and degree of impairment during trastuzumab therapy, confirming the global and uniform effect of trastuzumab on myocardial function.